MODEL OF INDUCTION MOTOR AS A PART OF THE CHANNEL OF ALTERNATE CURRENT OF AIRCRAFT ELECTRICAL POWER-SUPPLY SYSTEM - Y. P. Artemenko; A. G. Demchenko (Научный вестник МГТУ ГА)
Currently, there is an increasing level of electrified equipment of aircraft. This work is performed under the concept of creating a Fully Electric Aircraft (FEA), where the functions of the individual aircraft systems (pneumatic and hydraulic) will be performed by an electrical power system. The result of these procedures will be a significant increase of the electric motor load on board the aircraft. Consequently, it will increase the energy sources power of the power supply system (PSS) of the aircraft. This work is devoted to mathematical modeling of the induction motor. The induction motor with the squirrel-cage rotor is considered. The models of electrical and mechanical parts were considered while obtaining the induction motor mathematical model. It allows considering the relationship of electromagnetic and electromechanical processes in transient and steady-state modes of motor operation. The electrical part model is implemented in the equations for the voltages of windings and flux linkages circuits of the induction motor, which are written in the system of phase coordinates "ABC". When considering the mathematical model of the mechanical part the equation of torques, influencing the induction motor shaft during rotating action was used. The matrix equations system is the mathematical model of the induction motor. As a result of solving those equations the authors have got the formulae for stator winding current phases and squirrel-cage rotor circuits of the induction motor. The obtained mathematical model describes the electromagnetic and electromechanical processes in the induction motor, in a stationary system of phase coordinates "ABC". This model, unlike models in rotating coordinates "dq", describes the processes in symmetric and asymmetric modes, such as phase failures (open-phase modes) and short-circuit phases of the induction motor, while the mathematical model implemented in the system of rotating coordinates "dq", is true only for symmetrical modes of motor operation.